Bilateral diffuse anterior scleritis after unilateral cataract surgery: a case report - Matsuura, Kazuki; Ryu Uotani; Yoshitsugu Inoue (Journal of the Pakistan Medical Association, 2020)
Surgically induced scleritis (SIS) is a rare complication after a variety of ocular surgeries. Majority of the patients had had two or more surgical procedures before the onset of SIS. We report a patient who developed bilateral diffuse scleritis after unilateral cataract surgery. A 64-year-old man presented with red eye and tenderness in the right eye. An uneventful cataract surgery had been conducted in the right eye 5 months earlier. He had lost vision in the left eye 25 years ago, and there had been no ocular symptoms in both the eyes for the previous 20 years. Scleritis of the right eye appeared 5 months after cataract surgery, and scleritis of the left eye developed three months later. No previous reports referred to the possibility that the right eye surgery could induce scleritis in the left eye. Continuous...